Penguatan Pembukuan Unit Pengelola Keuangan Program Kota Tanpa Kumuh Kabupaten Trenggalek - Krissantina Eferyn; Nonni YAP; Nindi Vaulia Puspita; Oktaviana Wahyu Prihardina; Oktaviani Wahyu Prihardini (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Capacity building and development, both in the form of Strengthening Bookkeeping (due to changes in UPK officers, adjustments to existing activities and problems), so that UPK reporting as a form of accountability and transparency to the public can be maintained. Strengthening the capacity of UPK-LKM can also be related to the ability to provide guidance and assistance to community business groups that receive loans, this is so that KSMs as beneficiaries/loans of capital are not only asked to pay in installments but also provide guidance on the business being carried out and fostering existing group cohesiveness. The service method is carried out by first coordinating with the local manager and then carrying out the implementation of the financial management unit. The results of this study hope that they will be able to make their own financial reports when the Cities Without Slums empowerment program is completed. Later they will still be able to report the finances they manage to the community and village government. This training was welcomed by the UPK, they asked that this form of activity be held continuously/sustainably so that they could immediately feel the benefits.